Communication in dementia care: Experiences and needs of carers. (May 2022) - Nguyen, Hoang; Eccleston, Claire EA; Doherty, Kathleen Veronica; Jang, Sunny; McInerney, Fran
To ensure the well-being, quality of life and quality of care of people living with dementia, carers need to have the necessary communication knowledge and skills to respond appropriately to a person's changing abilities and needs. Understanding carers' communication experiences and needs in the context of dementia care is an important step in enabling effective education and support for carers. This study aimed to investigate communication challenges faced by carers and their coping strategies, influencing factors, and communication education and training needs. The sample involved 258 carers enrolled in an online dementia care program, and data were collected using a 16-item questionnaire. Descriptive statistics and non-parametric inferential statistics, including Chi-square, Mann–Whitney U, Kruskal–Wallis and Spearman's rho, were used to analyse the data. The participants reported experiencing a range of challenges in communicating with people living with dementia and employing various strategies in addressing these challenges, either independently or with the support of others. Improvements in a number of factors would be beneficial for carers, including more time for caring, more care and social support, as well as enhanced skills in communicating with people living with dementia. A large majority of the participants indicated their need for education or training in communication knowledge and skills, and those with higher learning needs were likely to be younger, care workers and other health professionals, and those with less care experience. Recommendations are made for future research and efforts to maximise effective education and support for carers of people living with dementia.